Reflective imaging of myelin integrity in the human and mouse central nervous systems - Craig, Georgina A.; Ryan, Lucy; Thapar, Jessica; McNamara, Niamh B.; Hoffmann, Alana; Page, Danielle; Rose, Jamie; Cox, Simon R.; Miron, Veronique E. (Frontiers in Cellular Neuroscience, 2024)
The structural integrity of myelin sheaths in the central nervous system (CNS) is crucial for maintenance of its function. Electron microscopy (EM) is the gold standard by which to visualize individual myelin sheaths. However, the tissue processing involved can induce artefacts such as shearing of myelin, which can be difficult to distinguish from true myelin abnormalities. Spectral Confocal Reflectance microscopy (SCoRe) is an imaging technique which leverages the differential refractive indices of compacted CNS myelin in comparison to surrounding parenchyma to detect individual compact myelin internodes with reflected light, positioning SCoRe as a possible complementary method to EM to assess myelin integrity. Whether SCoRe is sensitive enough to detect losses in myelin compaction when myelin quantity is otherwise unaffected has not yet been directly tested. Here, we assess the capacity of SCoRe to detect differences in myelin compaction in 2 mouse models which exhibit a loss of myelin compaction without demyelination: microglia-deficient mice (Csf1r-FIRE / ) and wildtype mice fed with the CSF1R inhibitor PLX5622. In addition, we compare the ability to detect compact myelin sheaths using SCoRe in fixed-frozen versus paraffin-embedded mouse tissue. Lastly, we show that SCoRe can successfully detect individual sheaths in aged human paraffin-embedded samples of deep white matter regions. As such, we find SCoRe to be an attractive technique to investigate myelin integrity, with sufficient sensitivity to detect myelin ultrastructural abnormalities and the ability to perform equally well in tissue preserved using different methods.